Susceptibility to COVID-19 in Pregnancy, Labor, and Postpartum Period: Immune System, Vertical Transmission, and Breastfeeding - Vale, Adson José Martins; Fernandes, Amélia Carolina Lopes; Guzen, Fausto Pierdoná; Pinheiro, Francisco Irochima; de Azevedo, Eduardo Pereira; Cobucci, Ricardo Ney (Frontiers in Global Women's Health, 2021)
The new coronavirus (SARS-Cov-2) was first identified in late 2019 as the new RNA virus in the coronaviridae family responsible for causing COVID-19 in the residents of China's Hubei province. In mid-March 2020 WHO declared the pandemic caused by this virus as a result of thousands of people infected all over the world. Epidemiological evidence obtained from other pandemics, such as influenza and ebola, suggest that pregnant women are more susceptible to serious complications and death from viral infection. Physiological changes in the anatomical structure of the respiratory system as well as in the immune system during the pregnancy-puerperal period seem to contribute to this greater risk. In fact, COVID-19 can alter immune responses at the maternal-fetal interface, affecting the well-being of both mother and her fetus. There is still no sufficient evidence in the literature to support the occurrence of vertical transmission and through breastfeeding, but the prevalence of prematurity was high among pregnant women infected by SARS-Cov-2. In this review, the changes in the immune system that may increase susceptibility to SARS-Cov-2 are discussed as well as the possible mechanisms involved in the transmission of the virus to the fetus by vertical transmission and during breastfeeding.